2009
DOI: 10.1021/pr900491n
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vaccinia Virus−Host Protein−Protein Interactions: Validations of Yeast Two-Hybrid Screenings

Abstract: Vaccinia virus, a large double-stranded DNA virus, is the prototype of the Orthopoxvirus genus, which includes several pathogenic poxviruses of humans, such as monkeypox virus and variola virus. Here, we report a comprehensive yeast two-hybrid (Y2H) screening for the protein−protein interactions between vaccinia and human proteins. A total of 109 novel vaccinia−human protein interactions were detected among 33 viral proteins. To validate subsets of those interactions, we constructed an ORFeome library of vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 36 publications
1
48
0
1
Order By: Relevance
“…By using automated Y2H technology, Myriad Genetics has generated a compilation of novel poxvirus-host PPIs (183). A total of 195 human proteins from a collection of four human cDNA libraries were identified as being putative binding partners for 33 different VACV proteins (Table 6).…”
Section: Virus-host-interacting Partnersmentioning
confidence: 99%
“…By using automated Y2H technology, Myriad Genetics has generated a compilation of novel poxvirus-host PPIs (183). A total of 195 human proteins from a collection of four human cDNA libraries were identified as being putative binding partners for 33 different VACV proteins (Table 6).…”
Section: Virus-host-interacting Partnersmentioning
confidence: 99%
“…Old reports showed that N2L is transcribed early during infection (55) and that a single mutation in its 5=-untranslated region is responsible for resistance to the inhibitor of RNA polymerase II (alpha-amanitin) and for the temperature-sensitive phenotype (56,57), but as yet there is no explanation for these observations. Moreover, a yeast two-hybrid assay revealed that N2 binds to importin alpha 1, valosin-containing protein (p97)/p47 complex interacting protein 1 (VCPIP1), and phospholipid scramblase 4 (PLSCR4) (58), but the biological significance of these interactions is unknown. Recently, it has been reported that the VACV N2L gene encodes a nonessential protein expressed early during infection and located in the nucleus that inhibits the activation of the IFN-␤ promoter by inhibiting IFN regulatory factor 3 (IRF3) activation (59), although the exact molecular mechanism of action remains unknown.…”
mentioning
confidence: 99%
“…By defining the interactions between viral and host proteins we will obtain a better knowledge on how viruses reproduce and cause disease, which may ultimately reveal novel targets for therapeutic intervention. Systematic maps capturing viral-host physical PPIs have been obtained using Y2H for Epstein-Barr virus [142], hepatitis C virus [143], several herpesviruses [144,145], vaccinia virus [146], influenza virus [147], dengue virus [148] and Tcell leukemia virus [149], and by AP-MS methodologies for HIV1 [150] and measles virus [151].…”
Section: The Human Interactome and Infectious Diseasesmentioning
confidence: 99%